mHealth - an Ultimate Platform to Serve the Unserved - Akter, S.; Ray, P. (Yearbook of Medical Informatics, 2010)
Objectives: To summarize major current developments and research in the field of mobile health (mHealth) services.Methods: Reports on the unique characteristics of mHealth platform and its role in delivering health services to the resource poor settings. Also, it evaluates different mHealth applications and identifies key success factors and challenges.Results and Conclusion: mHealth, based on the most ubiquitous and widely accepted technology, offers an unprecedented opportunity to serve the unserved by right time medical information services. There is growing evidence that it has already transformed healthcare delivery in many resource poor settings through its low cost, high reach and versatile applications. However, challenges still remain with regard to the development of consumer centric solutions, and services quality in terms of knowledge and competence of the provider, integration of the information systems and interoperability of the information services. Additional problems arise from the collaboration, partnership and regulation perspectives. There are noticeable trends towards solutions for these problems.
Keywords: mHealth; health information systems